THE IMPORTANCE AND STATE OF ECONOMETRIC MODELING IN FORECASTING THE DEVELOPMENT DYNAMICS OF THE CHEMICAL INDUSTRY - Sharipova Saodat Ubaydullaevna (Scholar Express Journals, 2025)
The article models the dynamics of the chemical industry development using econometric models. Initially, the article provides a brief description of scientific sources related to the topic. Then, issues such as the regression model, determination, correlation coefficients, the Durbin-Watson test, and empirical probability regarding the Fisher criterion are discussed. In the final section of the article, all the obtained results are summarized
Keywords: chemical industry; mining industry; development dynamics